Care of adolescents with depressive symptoms in a teaching clinic - Gedrat, Dóris Cristina; Schröder, Nádia Teresinha; da Silva, Daniela Souza (Seven Editora, 2023)
One of the spaces of recognized importance for the promotion of health are the clinic-schools, where multidisciplinary teams assist adolescents regarding the development of some psychological disorders, including depression. This study aimed to identify the perception of adolescents with depressive symptoms regarding the benefits of the care received at a teaching clinic that offers psychological services in the city of Manaus-AM. It is a research with a qualitative approach in which 10 adolescents aged 15 to 18 years old participated in 2020 and 2021. The data collected in the semi-structured interviews were analyzed according to thematic content analysis. The identified categories were: increased self-esteem; benefits in family relationships; benefits during the COVID 19 pandemic; decrease/absence of self-injury and other symptoms. These benefits may not mean a total remission of depressive symptoms, but there were positive changes in the quality of life of adolescents. DOI: https://doi.org/10.56238/methofocusinterv1-073